WONDER WOMAN (2017): AN AMBIGUOUS SYMBOL OF FEMINISM - Marinda P. D. Ghaisani (Rubikon : Journal of Transnational American Studies, 2019)
Wonder Woman is a popular fictional character who promotes the idea of an independent and powerful woman. Her name is glorified as she is assumed that she changes to the idea of the world being solely led and dominated by men. A remake film released in 2017 brings this popular character back into the silver screen. Despite being highly anticipated, not everyone supports Wonder Woman as an ideal symbol for women’s empowerment as dreamed by the feminists. Instead, the perception directed to Wonder Woman is divided into two lenses. One side believes that Wonder Woman is in line with the idea of feminism. In contrast, the other believes that she is the ideal example of a character who conforms to the standard set by patriarchal ideology.In investigating this idea, this paper applies Kate Millett’s concept of “personal is political” and how men and women’s roles in society have been passed down to the younger generation. The discussion illustrates that patriarchal power has infiltrated the character of Wonder Woman. Therefore, Wonder Woman becomes an ambiguous symbol when used for the women empowerment movement.Keywords: ambiguous; feminism; film; patriarchal power; Wonder Woman